2021
DOI: 10.1177/1352458520988149
|View full text |Cite
|
Sign up to set email alerts
|

Persistent severe lymphopenia 5 years after dimethyl fumarate discontinuation

Abstract: One known adverse event associated with dimethyl fumarate (DMF) is grade III lymphopenia which usually resolves within 2–3 months upon DMF discontinuation. Here, we report a case of a 50-year-old woman with MS who developed grade III lymphopenia within 6 months of DMF initiation, and despite treatment cessation within the next 6 months, she has continued to have severe persistent lymphopenia for over 5 years. Our observation suggests prolonged and possibly irreversible lymphopenia as a possible adverse event o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Fifty-three case reports and 10 case series were evaluated using the risk of bias assessment tool. Regarding case reports, 8 studies ( 33 , 37 , 42 , 58 , 67 , 70 , 75 , 81 ) had the highest methodological quality, together with 3 other studies ( 30 , 43 , 56 ) that similarly reported high quality information. For the remaining case reports, the risk of bias evaluation revealed mainly the lack of data on patients’ race and patients’ history presented as timeline.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three case reports and 10 case series were evaluated using the risk of bias assessment tool. Regarding case reports, 8 studies ( 33 , 37 , 42 , 58 , 67 , 70 , 75 , 81 ) had the highest methodological quality, together with 3 other studies ( 30 , 43 , 56 ) that similarly reported high quality information. For the remaining case reports, the risk of bias evaluation revealed mainly the lack of data on patients’ race and patients’ history presented as timeline.…”
Section: Resultsmentioning
confidence: 99%
“… 65 , 98 However, only a few cases have been reported of patients experiencing complications from prolonged severe lymphopenia. 65 , 97 , 99 , 100 Age ⩾50 years is another risk factor for PML; however, neither age ⩾50 years nor severe prolonged lymphopenia are absolute identifiers of those at increased risk of PML, with recorded case reports in patients without these characteristics. 95 , 101 103 …”
Section: Resultsmentioning
confidence: 99%
“…10%). 1 However, the article by Caldito et al 2 on a patient with DMF-induced grade III lymphopenia, which did not recover over a follow-up period of 5 years (last absolute lymphocyte count (ALC) 0.53 G/l), indicates the possibility of irreversible lymphopenia.…”
mentioning
confidence: 99%